ARE CHILDREN SMARTER (OR MORE SOCIALIZED) BECAUSE OF THE INTERNET? ARE CHILDREN SMARTER (OR MORE SOCIALIZED) BECAUSE OF THE INTERNET? - G'aniyeva, Hayriniso; G’aniyeva , Hamida (Maktabgacha taʼlim jurnali, 2022)
The Internet has enslaved children in particular since it is all they have ever known and grown up with. This is because today's children have lost their ability to keep themselves occupied. Are today's children smarter or more social as a result of their easy access to the entire world? That will be the subject of this journey through today's generation and their technological understanding. Today's youngsters are neither brighter nor more social because of the Internet.